Tyrėjo subjektyvaus patyrimo episteminė reikšmė lauko tyrimuose - Petružytė, Donata (Socialinė teorija, empirija, politika ir praktika, 2014)
Vilniaus universitetasSocialinio darbo katedraUniversiteto g. 9/1 – 309 kab.LT-01513 VilniusEl. paštas: donatai@gmail.com Straipsnio tikslas – išnagrinėti ir atskleisti tyrėjo subjektyvaus patyrimo episteminę reikšmę ir jo panaudojimo lauko tyrimuose galimybes. Šios temos nagrinėjimas svarbus, nes leidžia kritiškiau įvertinti lauko tyrimus, visapusiškiau traktuoti jų duomenis ir siekti didesnio jų validumo. Rengiant medžiagą straipsniui buvo taikomi mokslinės literatūros, metodinių pavyzdžių ir asmeninės patirties analizės metodai. Prieita prie išvados, kad atliekant tokio pobūdžio tyrimus svarbu fiksuoti ne tik tai, kas vyksta tyrėjo išorėje (t. y. tiriamoje erdvėje), bet ir tai, kas vyksta tyrėjo viduje, ir šiuos vidinius vyksmus traktuoti kaip intensyvių ir daugiamačių tyrėjo ir tiriamųjų sąveikų padarinius.Pagrindiniai žodžiai: lauko tyrimas, etnografinis tyrimas, stebėjimas dalyvaujant, reflektyvumas, tyrėjo savianalizė.The Epistemic Singnificance of Researcher’s Subjective Experience in Fieldwork Donata PetružytėSummary The key feature of fieldwork is the researcher’s immersion in the culture (i.e. the group or community) being investigated. For this reason, fieldwork requires an exceptionally deep and personal involvement and is, therefore, emotionally costly to the researcher. This article is specifically aimed at drawing readers’ attention to subjective experiences of the fieldworker, which are rarely discussed in the scientific literature. In essence, the objective of this article is to reveal the epistemological significance of a researcher’s subjective experience and to investigate the possibilities of its application to fieldwork. The primary methods of data collection for this article were analysis, synthesis, and interpretation of scientific literature and methodological illustrations. In addition, the author’s personal experience in fieldwork was also analysed (namely, her research about waste-gatherer communities in Lithuanian landfills, which was conducted in cooperation with Mindaugas Survila, the director and cameraman of the 2011 documentary “Field of Magic”). The author believes that the aforementioned topic deserves thorough research because of its potential to aid the critical evaluation of fieldwork, to allow a more versatile data interpretation, and to improve the validity of gathered data. On the one hand, the theoretical aspects of the problem are only briefly examined in this article. On the other hand, the practical strategies of encouraging social and psychological reflectivity are discussed extensively and personal experience is analysed meticulously. Despite the fact that this article deals with fieldwork in particular, some of its findings might be useful for qualitative research in general. It must be acknowledged that the social setting of the field has an inevitable impact on the ethnographer. The summary of the author’s personal reflections, ethnographic research, and methodological literature reveals five types of such impact: physiological, cognitive, social, emotional, and ethical. In each individual case, the combination of levels of influence and their intensity depend on three factors: research characteristics (duration, intensity of data collection, cultural proximity / distance between researchers and participants), the researcher’s personal qualities and experience, and the peculiarities of the social milieu being investigated. It is evident, that only through constant effort of reflection the pitfall of unconscious social conditioning can be avoided. Otherwise it might lie unnoticed and lead to gross misrepresentations of social reality. Naturally, researchers themselves also have a powerful effect on their group of research subjects as their sudden entrance in the field abruptly interrupts the course of habitual activities of these subjects. Research subjects also have particular expectations the researcher and their own attitudes based on individual experience or common sense. Consequently, it is extremely important for the researcher to master the art of identifying and negotiating these expectations and common sense notions in order to properly steer the process of entering the field. The level of mastery determines the type of data accessible to the researcher and how readily available it is. Generally speaking, there are several crucial aspects of the ethnographer’s influence on research subjects. Firstly, there is a number of primary characteristics of identity, determining the researcher’s personality and the conduct of research, which are beyond one’s control. Namely, they are gender, age, and ethnic background, which are associated with specific social norms. Secondly, there are a few factors that the scientist can control. They include his or her outlook, behaviour, and social skills. Despite being less fundamental, the latter are sometimes useful in mitigating the negative effects of the former. Accordingly, controllable and uncontrollable factors interact with the expectations of research subjects to create a particular image of the scientist. A dedicated role is fairly quickly assigned to the researcher, but it may be transformed in the course of the fieldwork. As each given role allows for a specific amount of social power, and the researcher’s power translates into freedom of inquiry, the fieldworker’s scientific endeavour is enhanced by attainment of powerful roles and limited by reception of powerless roles. Although the former statement has become fieldworkers’ common sense, a mere recognition of the fact does not suffice. In order to thoughtfully and efficiently handle the research process, fieldworkers need to delve deeply into the everyday interaction among their social roles, psychological characteristics, subjects’ expectations and dispositions about them and their research. Scientists must also evaluate their level of coping with all the tasks and how it advances or hinders data collection. It is clearly evident that knowledge about social life, as generated during fieldwork, has little to do with the controlled setting of a lab. Its life-like character is marked with intimate, long-term, complicated, and multidimensional relationship between the research parties. Hence, it is important to register not only the flow of events in the field that are external to the researcher, but also his or her inner processes and to treat them as a product of multifaceted interaction between the fieldworker and natives of the field. It is quite apparent that because of a multitude of reciprocal effects between ethnographers and the field, researchers cannot be regarded as infallible and objective means of research. Henceforth, regular efforts by the researcher to analyse this complicated relationship from one’s point of view are mandatory. These efforts might provide a fruitful insight into research development and data interpretation. In conclusion, reflecting should be a vital part of every ethnographer’s research, because it would bring a handful of improvements. Firstly, the proper reflection on processes within the field and the self-analysis might lead to an increased observational acuteness. This would account for richer data and more in-depth information about the research object. Secondly, regular self-analysis would allow the fieldworker to be more involved in the research process and improve his or her ability to make strategic moves. Thirdly, acute reflection could shed more light on the context of data and the procedure of their collection. Furthermore, this would lead to a both more apt attribution of meaning during data interpretation and an improved validity of data. As a bonus, self-analysis may relieve the emotional burden put on the researcher by the difficulties of fieldwork and encourage the fieldworker’s personal development. Finally, deep reflection might also serve the educational purpose for both authors and readers alike, since it enriches research reports with detailed accounts of the fieldwork peculiarities. Key words: field research, ethnographic research, participant observation, reflectivity, researcher’s self-analysis